PENDIDIKAN SOSIAL EMOSIONAL ANAK USIA DINI MELALUI METODE BERMAIN PERAN (ROLE PLAYING) DI KELOMPOK B USIA 5-6 TAHUN DI TK BENTENG 1 KEPULAUAN SELAYAR - Riskal Fitri (AIJER: Algazali International Journal Of Educational Research, 2019)
Abstract: The Emotional Social Education of Early Childhood through Role Playing Method in Group B Age 5-6 Year at TK Benteng 1 Selayar Island. This study aimed to develop the Children's Emotional Social Through Role Playing Method. This type of research was Classroom Action Research (CAR). Data collection consisted of observations, interviews, and documentation. Data Analysis was carried out in a series of steps with several cycles. Based on the results of data analysis and discussion in cycle I and cycle II, it could be seen from an increase in children's social emotional abilities, very well-developed students/BSB in the cycle I of the first meeting with indicators of understanding and obeying the rules achieved 6.25%, while indicators patiently wait their turn reached 6.25%. At the second meeting with indicators understanding and obeying the rules it reached 6.25%, while indicators patiently waiting their turn reached 12.5%. The third meeting with indicators understanding and obeying the rules reached 18.75%, while indicators patiently waited their turn reached 12.5%. Then in the cycle II the first meeting with indicators to understand and obey the rules reached 37.5%, while indicators patiently waited their turn reached 12.5%. At the second meeting with indicators understanding and obeying the rules reached 62.5%, while indicators waiting patiently reached 62.5%. The third meeting with indicators understanding and obeying the rules reached 87.5%, while indicators waiting for their turn reached 87.5%.